Financial Technology and Financial Literacy in Shaping Generation Z’s Stock Investment Intention: The Mediating Role of Risk Tolerance - Chusnul Maulidina Hidayat; Kurnia Indah Sumunar (Global Research Collaboration, 2026)
The development of digital technology has significantly transformed the financial sector, particularly through Financial Technology (FinTech) innovations that facilitate public access to investment services. This phenomenon has also encouraged the participation of the younger generation, especially Generation Z, in stock investment within the capital market. However, the ease of access to technology is not always accompanied by an adequate understanding of investment concepts and risks, making financial literacy a crucial factor. In addition, psychological aspects such as risk tolerance also play an important role in influencing individual investment decisions. This research investigates how financial technology and financial literacy has an effect on Generation Z’s intention to invest in stocks, while considering risk tolerance as a moderating factor. The study adopts a quantitative research design and collects data through a survey distributed to Generation Z participants, with the collected data then being processed using Structural Equation Modeling with the Partial Least Squares approach. The results demonstrate that financial technology, financial literacy, and risk tolerance each have a positive and statistically significant effect on Generation Z’s stock investment intention. Furthermore, risk tolerance strengthens the effect between financial technology, financial literacy, and the intention to invest in stocks. These findings imply that improving financial literacy and maximizing the utilization of financial technology can encourage greater participation of Generation Z in stock market investment. Future studies are recommended to incorporate additional variables and involve a larger and more diverse group of respondents in order to provide more comprehensive insights.